2014
DOI: 10.5664/jcsm.3452
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnographic Investigation of Sleep and Respiratory Parameters in Women with Temporomandibular Pain Disorders

Abstract: Study Objectives: Temporomandibular pain disorders (TMD) and myofascial pain were linked to increased prevalence of insomnia and obstructive sleep apnea (OSA) on clinical grounds. However, the literature lacks an accurate polysomnographic (PSG) characterization of sleep abnormalities associated with TMD, given that prior studies included small or uncontrolled samples of TMD patients. The present investigation aims to objectively evaluate measures of sleep and respiratory disturbance in a large representative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 25 publications
1
67
1
2
Order By: Relevance
“…Cases and controls were similar in both exclusion rates and demographic composition, as reported elsewhere. 19,21 …”
Section: Methodsmentioning
confidence: 99%
“…Cases and controls were similar in both exclusion rates and demographic composition, as reported elsewhere. 19,21 …”
Section: Methodsmentioning
confidence: 99%
“…One must consider, however, that tinnitus and chronic TMD are commonly present in patients with a similar psychological profile, characterized by the presence of significant distress and impairment (HILGENBERG et al, 2012), and with a high prevalence in females (DUBROVSKY et al, 2014), the observed intensity of discomfort from tinnitus being significantly higher in women (COELHO; SANCHEZ; BENTO, 2004). Of the 44 individuals evaluated in this study, 37 (84%) were women, with a mean age of 43.2 ±2.1 years.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in patients with concomitant obstructive sleep apnea and sleep bruxism, most sleep bruxism events occurred after apnea-hypopnea events, suggesting that sleep bruxism events occurring close to apnea-hypopnea events is a secondary form of sleep bruxism [29] [30]. Further evidence suggest that myofascial pain in TMJ and POF disorders is associated with mild elevation in sleep fragmentation and increased frequency of RERA events [4].…”
Section: Introductionmentioning
confidence: 95%
“…TMJ disorders (TMJD) as part of masticatory disorders (MD), most often but not always characterized by painful musculoskeletal signs and symptoms in the masticatory and associated structures in head, neck and shoulder area, estimated to affect approximately 5% to 15% of the population, predominantly women [1] [2] [3] [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation